Clinical features, damage accrual, and survival in patients with familial systemic lupus erythematosus: data from a multi-ethnic, multinational Latin American lupus cohort. (August 2020) - Quintana, Rosana; Pons-Estel, Guillermo J; Roberts, Karen; Sacnún, Mónica; Serrano, Rosa; Nieto, Romina; Conti, Silvana; Gervasoni, Viviana; Catoggio, Luis J; Soriano, Enrique R; Scolnik, Marina; García, Mercedes A; et al.
Objectives: This study aimed to compare the clinical features, damage accrual, and survival of patients with familial and sporadic systemic lupus erythematosus (SLE). Methods: A multi-ethnic, multinational Latin American SLE cohort was studied. Familial lupus was defined as patients with a first-degree SLE relative; these relatives were interviewed in person or by telephone. Clinical variables, disease activity, damage, and mortality were compared. Odds ratios (OR) and 95% confidence intervals (CI) were estimated. Hazard ratios (HR) were calculated using Cox proportional hazard adjusted for potential confounders for time to damage and mortality. Results: A total of 66 (5.6%) patients had familial lupus, and 1110 (94.4%) had sporadic lupus. Both groups were predominantly female, of comparable age, and of similar ethnic distribution. Discoid lupus (OR = 1.97; 95% CI 1.08–3.60) and neurologic disorder (OR = 1.65; 95% CI 1.00–2.73) were significantly associated with familial SLE; pericarditis was negatively associated (OR = 0.35; 95% CI 0.14–0.87). The SLE Disease Activity Index and Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI) were similar in both groups, although the neuropsychiatric (45.4% vs. 33.5%; p = 0.04) and musculoskeletal (6.1% vs. 1.9%; p = 0.02) domains of the SDI were more frequent in familial lupus. They were not retained in the Cox models (by domains). Familial lupus was not significantly associated with damage accrual (HR = 0.69; 95% CI 0.30–1.55) or mortality (HR = 1.23; 95% CI 0.26–4.81). Conclusion: Familial SLE is not characterized by a more severe form of disease than sporadic lupus. We also observed that familial SLE has a higher frequency of discoid lupus and neurologic manifestations and a lower frequency of pericarditis.